Design of a millimeter-wave wideband filtering balun in GaAs IPD technology - Li, Yijun; Ni, Jinxuan; Li, Siyu; Han, Qian; Tian, Jie; Li, Na; Ma, Tianye (Frontiers in Physics, 2025)
This article introduces a novel microstrip filtering balun designed using GaAs Integrated-Passive-Device (IPD) technology, aimed at addressing the needs of millimeter-wave communication applications such as Wireless Personal Area Networks (WPAN) and Wireless Local Area Networks (WLAN). The design leverages a wavelength transmission line for phase inversion and coupling structures to enhance frequency selectivity. A prototype was fabricated and tested, demonstrating a center frequency of 45.6 GHz, a relative bandwidth of 59.2%, and a phase difference of 180° (±7.0°) between the output ports. Simulations and measurements confirm the design’s excellent bandwidth and selectivity, showcasing its potential for integration into compact, high-performance communication systems.